The potential of biostimulants on soil microbial community: a review - Adedayo, Afeez Adesina; Babalola, Olubukola Oluranti (Frontiers in Industrial Microbiology, 2023)
To improve agricultural sustainability, an agriculturally-productive system is required to maintain soil fertility and reduce the loss of soil biodiversity. One of the modern technologies employs microbial biostimulants that ascertain abundant agricultural yield with high nutritional values, subduing disadvantages obtained from environmental changes. This review aimed to provide knowledge on the effects of biostimulants on microbial communities' potential to promote agricultural production. Plant biostimulants are novel materials applied in the farming sector nowadays to improve crop yield and occur as usual in plant seeds and as an alternative to chemical derivative application on crop plants. Microbial biostimulants function as biological inputs to increase cropfruit production and reduce the decomposition of soil. In conclusion, the application of biostimulants necessitates the accomplishment of an absolute choice of beneficial microbes as well as the potential to combat problems that can be faced later in the agricultural sector.